If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + 14 = -12 Reorder the terms: 14 + 13x = -12 Solving 14 + 13x = -12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 13x = -12 + -14 Combine like terms: 14 + -14 = 0 0 + 13x = -12 + -14 13x = -12 + -14 Combine like terms: -12 + -14 = -26 13x = -26 Divide each side by '13'. x = -2 Simplifying x = -2
| 9x^2+144x+576=0 | | 9x+28-7x=-3.3 | | 5n-3(n-8)=4+3n | | 4=w/12 | | y-5+5= | | 11-4a=-7(a-1)+1 | | -(2x+3)=-5+7x | | 3x-3-x-4x=5x+12-12x | | b^2-4b+1=-5 | | 9(y-1)=4y+4 | | -6(r+6)=-37-5r | | -6b-6b=8-4b-7b | | p+7=8 | | (-x)-2x=(-7) | | 2=2-7n-2n | | 3x+4-2x-x=4x-4 | | -2(5x+5)+2x-1=-43 | | -2+3x=-6+7(6x-5) | | 5/k=2/7 | | 20-22+3= | | 2n+40=2n+10 | | 10=x*(x+3x) | | 8/3=5/b | | 4(8n-3)=-12+7n | | n/7=4/3 | | X^2(2x+3y-6)= | | 0=-16t^2+16t+672 | | cos(2x)*sin(4x)=0 | | -2x-4.5+7=1.8 | | 3/x=18 | | r/3=4/2 | | 12-7x=24x+23 |